P02 Promotion of Active Transportation among State Departments of Transportation in the US. Issue 2 (June 2015) - Dill, Jennifer
Abstract: Background: In the U.S., state departments of transportation (DOTs) play a key role in planning, designing, and building transportation infrastructure, as well as setting broad policy. DOTs historically have focused on highways, but their scope has been expanding. Starting in 1991, each state DOT must have a pedestrian and bicycle coordinator and must describe their bicycle and pedestrian programs in long-range plans. This research examines how and why state departments of transportation adopt policies that support active transportation. Methods: Data were first collected from official state DOT long-range plans and guidance documents on the following topics. Second, we conducted a survey of state DOT bicycle and pedestrian coordinators. These data were supplemented with data on population, land use characteristics, and transportation infrastructure from federal agency sources. Results: (Only partial results presented here.) Just over half (53%) of states also had a bicycle and pedestrian plan and half of the states (51%) have a bicycle and pedestrian advisory committee. Over two-thirds of the state DOTs support, or at least mention, the following active transportation elements: Coordination with land-use agencies; Retrofitting streets with pedestrian and bicycle accommodations; Pedestrian- and transit-friendly site designs; Crosswalks; Bike lanes; Multi-use trails and paths; Developing missing links in trail systems; and Traffic calming. Less than one-third of DOTs explicitly supported the following: Increasing density and mixed-use development; Road diets and narrow or "skinny" streets; Rail transit for everyday travel; Weather protection along sidewalks; and providing clear views of pedestrians for drivers when exiting (a parking facility) to the street. The degrees of support for active-living related innovation, as expressed in DOT plans, were totaled for each state. There is no clear relationship between overall population size and level of innovation. There was a significant positive correlation ( r =0.39, p<0.01) between the percentage of states' population in urban areas and level of innovation. States with land-use agencies show significantly higher support for active living-related innovation in their plans than states without state land-use agencies (p<0.05). There is no significant correlation between vehicles per capita and DOT innovation. However, there is a significant negative correlation between fuel consumption per household and innovation ( r =−0.34, p<0.05). This is likely linked to the level of urban living. Conclusions: The overall levels of support for active transportation in state DOT plans and guidance varies, and appears related to levels of urbanization. Overall, the level of commitment to more innovative policies, e.g. road diets, is minimal.